Novel Long Noncoding RNA 005620 Induces Epirubicin Resistance in Triple-Negative Breast Cancer by Regulating ITGB1 Expression - Wang, Fengliang; Yang, Sujin; Lv, Mingming; Chen, Fei; Yin, Hong; Gao, Sheng; Tang, Jinhai; Yu, Jing (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) is often treated with anthracyclines (e.g., doxorubicin or epirubicin), but very little is known about anthracycline resistance, especially epirubicin resistance in TNBC. To identify novel long noncoding RNAs (lncRNAs) involved in epirubicin resistance in TNBC, we established a new TNBC MDA-MB-231 cell line that was resistant to epirubicin (Epi-R). A total of 12 differentially expressed lncRNAs were identified using RNA sequencing analysis of Epi-R cells. Among these lncRNAs, we found a novel intronic lncRNA, lnc005620, was highly expressed in Epi-R cells and human TNBC tissues. Further gain- and loss-of-function studies demonstrated that lnc005620 played an oncogenic role and partially abrogated the effects of epirubicin on TNBC cells. Using iTRAQ proteomics analysis, we found that three members of the integrin family, integrin β4, integrin β1 and integrin α6, were all upregulated in Epi-R MDA-MB-231 cells. Integrin β1, encoded by the ITGB1 gene, was validated to be a downstream target of lnc005620 in Epi-R MDA-MB-231 cells. Our study demonstrates that novel lnc005620 promotes TNBC progression and chemoresistance to epirubicin via integrin β1 both in vitro and in vivo and provides a promising therapeutic target for TNBC patients in terms of enhancing the benefits of epirubicin treatment.